2014
DOI: 10.1111/are.12391
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of autochthonous bacterial communities in the intestinal mucosa of grass carp (Ctenopharyngodon idellus) (Valenciennes) determined by culture-dependent and culture-independent techniques

Abstract: Traditional culture-based technique and 16S rDNA sequencing method were used to investigate the mucosa-associated autochthonous microbiota of grass carp (Ctenopharyngodon idellus). Twenty-one phylotypes were detected from culturable microbiota, with Aeromonas, Shewanella, Lactococcus, Serratia, Brevibacillus, Delftia, Pseudomonas, Pantoea, Enterobacter, Buttiauxella and Yersinia as their closest relatives. Genomic DNA was directly extracted from the gut mucosa of C. idellus originating from six different geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 64 publications
2
35
2
Order By: Relevance
“…; Li et al . ), and our results showed significant differences with those of previous reports. The differences might be caused by habitat differences or variations in feeding habit; habitat and feeding habit are the two major factors that affect gut microbiota (Cahill ; Ingerslev et al .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…; Li et al . ), and our results showed significant differences with those of previous reports. The differences might be caused by habitat differences or variations in feeding habit; habitat and feeding habit are the two major factors that affect gut microbiota (Cahill ; Ingerslev et al .…”
Section: Discussioncontrasting
confidence: 99%
“…Our results were consistent with those obtained previously (Li et al . ). Brevundimonas , Massilia , Curvibacter , Acinetobacter and an unclassified Clostridiales genus were the dominant genera in herbivorous M. amblycephala .…”
Section: Resultsmentioning
confidence: 97%
“…Bradyrhizobium is Gram‐negative bacteria and important for nitrogen fixation (Ramírez‐Bahena et al., ). The genus of Bradyrhizobium was ever found in the intestines of sea bass ( Dicentrarchus labrax ) and grass carp ( Ctenopharyngodon idellus ), but its function in these fish was not well studied (Carda‐Diéguez, Mira, & Fouz, ; Li, Zhong, et al., ). Cetobacterium is Gram‐negative bacteria common observed in the intestines of freshwater fish (Larsen et al., ; Li, Long, Gatesoupe, Zhang, Li, & Gong, ; Tsuchiya, Sakata, & Sugita, ).…”
Section: Discussionmentioning
confidence: 99%
“…The dominant genus identified in the gut microbiota of Giant‐Mottled eels and Shortfin eels were Acinetobacter , Mycoplasma and Shewanella and Bacteroides and Mycoplasma. Acinetobacter is Gram‐negative bacteria, and it was ever isolated from intestines of fish (Ingerslev et al., ; Li, Zhong, et al., ). A previous research reported that the Acinetobacter has the ability to produce the inhibitory substances against the V. anguillarum , which could infect freshwater eels (Spanggaard et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Information on the archaeal communities associated with the fish gut is scarce, but Archaea have been detected in fecal or intestinal samples of European flounder Platichthys flesus (van der Maarel et al, 1998(van der Maarel et al, , 1999, gray mullet (van der Maarel et al, 1998Maarel et al, , 1999, gilthead seabream Sparus aurata (Kormas et al, 2014), and grass carp Ctenopharyngodon idella (Ni et al, 2014;Xia et al, 2014). Although information is not available for archaeal abundance, the archaeal diversity appears considerably lower than that of the bacterial communities in the fish GI tract (Li et al, 2014;Ni et al, 2014). For example, metagenomic sequencing revealed that the grass carp microbiome contained 1112 bacterial phylotypes and only 116 Archaea phylotypes (Ni et al, 2014).…”
Section: Microbial Compositionmentioning
confidence: 99%